The role of marine salt and surfactants in the decline of tyrrhenian coastal vegetation in Italy - Bussotti, F; Grossoni, P; Pantani, F (Annales des Sciences Forestières, 1995)
The decline of coastal vegetation is a phenomenon affecting some areas of the Mediterranean region and Australia; it is due to the presence of surfactants in marine aerosols, a consequence of sea pollution by detergents. This paper gives some observations made at various sites along the Tyrrhenian coast in Italy. The authors show that the presence of surfactants in the environment correlates with the presence of sea salt, and that the impact of surfactants on vegetation is local and occurs in association with strong sea winds. The study of the synergistic effect of surfactants and sea salt on the crowns of trees exposed to aerosols suggests that the surfactant can cause direct damage, while the absorption of sea salt is enhanced by the presence of the surfactant only when exposure to aerosol is prolonged, or if it is administered in very high concentrations.
Keywords: crown damage; leaf absorption; marine aerosol; NaCl; Pinus pinea L; surfactant

Elemental leaching from Quercus ilex L. in response to simulated acidic fog - Paoletti, E; Udisti, R; Pantani, F; Barbolani, E (Water, Air, & Soil Pollution, 1989)
Quercus ilex L. seedlings were intermittently exposed to simulated acidic and non-acidic fogs in 6-hr events for 16 times. After a 1-mo break, treatments were carried out again for a 5 day period. Strong acidity neutralization, weak acidity release and cation leaching from foliage and stem were determined. Leaching of AI, Cu, Mn, Fe, Cd, Pb, Ca, Mg, and K increased in response to acid treatment. This effect was less marked for Na. A positive correlation between H ÷ uptake and cation leaching was found. Cationic release and neutralization of strong acidity increased after breaks in acid treatment, but this faculty and the a m o u n t of leached cations and neutralized acidity decreased with time. The stem showed a higher cation loss and higher buffer capacity than the leaves.
Keywords: acidity; Cations (voyant); foliar leaching